Behavioral Strategies to Prevent and Mitigate COVID-19 Infection (2020)
The single stranded RNA virus SARS-CoV-2 has caused a massive addition to the already leading global cause of mortality, viral respiratory tract infections. Characterized by and associated with early and deleteriously enhanced production of pro-inflammatory cytokines by respiratory epithelial cells, severe COVID-19 illness has the potential to inflict acute respiratory distress syndrome and even death. Due to the fast spreading nature of COVID-19 and the current lack of a vaccine or specific pharmaceutical treatments, understanding of viral pathogenesis, behavioral prophylaxis, and mitigation tactics are of great public health concern. This review article outlines the immune response to viral pathogens, and due to the novelty of COVID-19 and the large body of evidence suggesting the respiratory and immune benefits from regular moderate intensity exercise, provides observational and mechanistic evidence from research on other viral infections that suggests strategically planned exercise regimens may help reduce susceptibility to infection, while also mitigating severe immune responses to infection commonly associated with poor COVID-19 prognosis. We propose that regular moderate intensity exercise should be considered as part of a combinatorial approach including widespread hygiene initiatives, properly planned and well-executed social distancing policies, and use of efficacious facial coverings like N95 respirators. Studies discerning COVID-19 pathogenesis mechanisms, transfer dynamics, and individual responses to pharmaceutical and adjunct treatments are needed to reduce viral transmission and bring an end to the COVID-19 pandemic.